2001
DOI: 10.1103/physrevb.63.155415
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of concentric-shell fullerenes from electron-energy-loss spectroscopy in transmission

Abstract: Electronic structure and optical properties of concentric-shell fullerenes from electron energy-loss spectroscopy in transmission Pichler, T.; Knupfer, M.; Golden, M.S.; Fink, J.; Cabioc'h, T. Published in:Physical Review B Link to publication Citation for published version (APA):Pichler, T., Knupfer, M., Golden, M. S., Fink, J., & Cabioc'h, T. (2001). Electronic structure and optical properties of concentric-shell fullerenes from electron energy-loss spectroscopy in transmission. Physical Review B, 63, 155415… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…filled in the ground state. 3,28 This tendency was, however, implicitly challenged recently, 11 and the resolution of these conflicting views is taken up in Sec. III C.…”
Section: A C 1s Excitationsmentioning
confidence: 99%
“…filled in the ground state. 3,28 This tendency was, however, implicitly challenged recently, 11 and the resolution of these conflicting views is taken up in Sec. III C.…”
Section: A C 1s Excitationsmentioning
confidence: 99%
“…Sufficient quantities could be produced for investigation of their optical, electronic and tribological properties. [14][15][16][17] These carbon onions were characterized by Fourier transform infrared ͑FTIR͒ spectroscopy 16 and it was shown that the most stable state for the onions consists of concentric spheres of fullerenes C n ͑n = 60, 240, …͒. Until now, the electronic properties of the onions were characterized only by spatially resolved EELS in transmission 15,18 and reflection mode.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] These carbon onions were characterized by Fourier transform infrared ͑FTIR͒ spectroscopy 16 and it was shown that the most stable state for the onions consists of concentric spheres of fullerenes C n ͑n = 60, 240, …͒. Until now, the electronic properties of the onions were characterized only by spatially resolved EELS in transmission 15,18 and reflection mode. 19 Recently Sano et al [20][21][22] reported the production of several milligrams of carbon onions with diameters ranging from 4 to 36 nm using an arc discharge between two graphite electrodes submerged in water or liquid nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above discussion on the π 2 mode confinement, the π + σ peak might then be expected to be show nondispersive behavior for the (13,7) tube. Indeed, such an effect is observed for C 60 [51] as well as at the tip of a multilayer graphene cone [27]. However, no localization of the π + σ mode along the tube axis is apparent for the (13,7) SWCNT in Figs.…”
Section: Momentum-resolved Valence Loss Spectramentioning
confidence: 86%